Platonic Henology vs. Aristotelian henology - from methexis to mimesis - Olesiński, Dariusz (Folia Philosophica, 2003)
The purpose of this article is to present an outline of Platonic and Aristotelian henology in the light of differences and dissimilar consequences that follow from them mainly with respect to ontology. The author claims that the essence of the Platonic henology, which is fundamentally based on the principle of the difference (binarity), is a dialectical exploration of one-many relationship and a disclosure of the basic role that this relationship plays in the structure of reality. On the other hand Aristotelian henology, which is mainly grounded on the systematical analysis of different meanings of oneness is based on the idea of sameness (identity) and on Aristotle’s doctrine of substance.